Improving the Efficiency of Product and Spare Parts Storage Space. Case Study: Air Conditioner Manufacturing Company - แก่นละออ, นุชจรี; สุวกุลศิริ , จุติพร; ทองสุข , พิธิวัฒน์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
From a study on improving the efficiency of product and spare parts storage areas. Case study: Air conditioner manufacturing company. The objectives are: 1.To collect data, work procedures, and study problems that occur in the warehouse. 2.To classify products by using a mixed combination system, organize the warehouse layout, and apply the Visual Control system to determine the storage area. 3.To compare the working time in the product withdrawal process before and after the improvement. From collecting data and analyzing the problem using the 5G theory, it was found that there were 121 items in total, which were air conditioners imported from the port. Some products had more stock than others, so they had to replace other products with a large number of products, resulting in the products being placed in the wrong positions, which took a long time to search and withdraw products.Therefore, the researcher classified the products into 4 groups according to the product type and rearranged the product placement and made product type indicators. Compare the results of increasing the efficiency of warehouse management. By measuring the time taken to pick goods before and after the warehouse adjustment 30 times, it was found that the average time before the adjustment was 15.13 minutes. After the adjustment, the average time taken to pick goods was 12.23 minutes, a decrease of 19.16 percent.